Familial influences on the division of household labour in Malaysian families - Harn, Shian Boo (Penerbit Universiti Kebangsaan Malaysia, 2020)
Gendered division of household labour is a social issue facing many countries. However, there is limited available research on this issue in Malaysian context. Scholars raise the possibility that differences across racial and ethnic groups are due to differences in historical experiences and cultural background, which may condition the symbolic meanings of daily activities. This possibility remains under-researched in Malaysia. This study examines the gendered experiences of division of household labour among Malay and Chinese couples in Malaysia and reasons given for it. A qualitative semi-structured interview was conducted with 30 respondents (18 women and 12 men) in Malaysia. The respondents consist of 15 Malays and 15 Chinese. The interview findings suggest there are three themes emerged related to the familial influences on couples’ domestic behaviours: (1) the way female interviewees see their father’s and brothers’ attitude towards housework influencing their expectation of their spouse, (2) the way female interviewees see their mother’s attitude towards housework influencing their own attitudes, and (3) the way male interviewees were expected by their mothers to engage in housework. These findings suggest that parents are influential in shaping their children’s attitudes and therefore their contribution to housework tasks after they form their own families. It also indicates the importance of ethnic identity in influencing the way couple engage in and share housework. This study adds insight to the complexities of the factors that may allow couples to move towards a more equal division of household labour.